EFFORTS OF INDONESIA AND SINGAPORE IN INCREASING FOREIGN DIRECT INVESTMENT (FDI) COOPERATION THROUGH BILATERAL INVESTMENT TREATY (BIT) DURING THE COVID-19 PANDEMIC - Fadhilah Nur Amalina (Mediasi: Journal of International Relations, 2022)
The Covid-19 pandemic has caused economic uncertainty for world countries, especially Indonesia and Singapore.The two countries experienced a decline in Gross Domestic Product (GDP) income, causing a deficit in the StateRevenue and Expenditure Budget (APBN). This has hampered the performance of Singapore's FDI in Indonesia. Inovercoming the impact of the pandemic, the two countries made an effort to restore the economy by strengtheninginvestment cooperation through the Bilateral Investment Treaty (BIT). This cooperation is carried out to exchangebenefits for the sake of the economic recovery process and mutual support in economic activities.This study aims tofind out how Indonesia and Singapore are trying to increase Foreign Direct Investment (FDI) cooperation throughthe Bilateral Investment Treaty (BIT) during the Covid-19 pandemic. To explain this issue, researchers use the conceptof bilateral cooperation as a basis for implementing the agreement and the Harrod-Damor Foreign Direct Investmentconcept which is an investment strategy in Indonesia. The research results show that the presence of a BIT agreementbetween Indonesia and Singapore can increase the intensity of FDI cooperation. This is because the BIT provides aclear and strong regulatory framework for investors from both countries so that it becomes a special attraction. Apartfrom that, to increase investment attractiveness, Indonesia and Singapore have a forum, namely the IndonesiaSingapore Business Council (ISBC). This forum is a forum for promoting domestic business to be better known byinvestors from Indonesia and other partners affected by the investment made by Singapore. Investment activities canincrease the rate of economic growth and generate long-term benefits for the two countries.